Farms of the future guidelines - Jones, E.; Arango, D.; Ramírez Villegas, Julián Armando; Bonilla Findji, Osana; Bailey M; Chaudhury A; Sova, Chase; Thorn, J.; Helfgott, Ariella E.S.; Jarvis, Andy (2014)
The farms of the future (FOTF) approach is an interactive climate adaptation, knowledge sharing and learning experience that transforms climate forecasts into field-based realities by physically taking participants on a journey to areas that already experience climatic conditions that represent plausible future climate scenarios. The hypothesis behind this is that the knowledge exchange process can enhance a farmer’s/village’s capacity to adapt to changing climatic conditions by exposing them to innovative farming communities that have already successfully adapted their agricultural practices to various distinct climatic conditions the reference village might experience.